2020
DOI: 10.1039/d0bm01183e
|View full text |Cite
|
Sign up to set email alerts
|

Immunostimulatory biomaterials to boost tumor immunogenicity

Abstract: Cancer immunotherapy is exhibiting great promise as a new therapeutic modality for cancer treatment. However, immunotherapies are limited by the inability of some tumors to provoke an immune response. These...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 189 publications
(293 reference statements)
1
10
0
Order By: Relevance
“…Our findings indicated that tumor-mediated tolerance or barriers could be overcome by radiation-induced systemic antitumor responses in highly immunogenic tumors and primed CD8 T cells could recognise and attack both local tumors and distant tumors outside the radiation field. In contrast, low immunogenicity indicated that TAAs were downregulated in tumors and evasion of host immunity occurred in the tumor microenvironment, which lacked chemokine-mediated trafficking and showed poor adaptive immune cell activation ( 8 , 11 ). The rarity of the abscopal effect suggests that even primed antitumor CD8 T cells could not overcome a suppressive tumor microenvironment with low infiltration of responding immune cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings indicated that tumor-mediated tolerance or barriers could be overcome by radiation-induced systemic antitumor responses in highly immunogenic tumors and primed CD8 T cells could recognise and attack both local tumors and distant tumors outside the radiation field. In contrast, low immunogenicity indicated that TAAs were downregulated in tumors and evasion of host immunity occurred in the tumor microenvironment, which lacked chemokine-mediated trafficking and showed poor adaptive immune cell activation ( 8 , 11 ). The rarity of the abscopal effect suggests that even primed antitumor CD8 T cells could not overcome a suppressive tumor microenvironment with low infiltration of responding immune cells.…”
Section: Discussionmentioning
confidence: 99%
“…Cancer cells that can elicit a protective immune response to inhibit tumor growth are considered to have high immunogenicity. Conversely, cancer cells that only stimulate a weak immune response and fail to control tumor growth are classified as having poor immunogenicity ( 8 ). In this study, we observed the efficacy of radiotherapy in both highly and poorly immunogenic tumor models and found that single high-dose radiation was optimal for stimulating a localised antitumor immune response and provided an opportunity to boost abscopal response rates in highly immunogenic tumors.…”
Section: Introductionmentioning
confidence: 99%
“…Injectable or implantable hydrogels and scaffolds, representative of 3D macroscale biomaterials, facilitate the controlled delivery and release of therapeutic small molecule reagents, macromolecule biological factors, and even living cells strikingly heightening the vitality of cancer immunotherapy [ 29 ]. Unfortunately, clinical translations of 3D macroscale biomaterial-based immunotherapies still develop in a slow graded pace during several decades [ 30 , 31 ]. More and more widely recognized, it is essential for the biomaterial engineering researchers to attain a systematic characterization and comprehensive understanding of the mutual interaction between biomaterials and immune system, including how the physicochemical and mechanical properties of the particular biomaterial system influence the immunologic behaviours, and how immunologic indexes fluctuate towards different biomaterial systems upon timescales, in order to speed up their clinical developments [ 7 , 32 , 33 ] ( Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, novel immunotherapeutic agents are warranted to overcome this limitation by changing the TME through the depletion of cancer-promoting microenvironmental cells and their reeducation toward immune-stimulating, tumor-suppressive phenotypes [ 13 ]. This strategy is now widely appreciated as an anticancer armamentarium [ 13 , 14 ]. Oncolytic virus (OV) is one of the most promising treatment strategies for solid malignancies [ 15 ] because it can remodel the TME toward a T cell-inflamed phenotype by stimulating host immune responses against the tumor [ 12 ].…”
Section: Introductionmentioning
confidence: 99%